2017
DOI: 10.5588/pha.16.0102
|View full text |Cite
|
Sign up to set email alerts
|

Routine implementation of isoniazid preventive therapy in HIV-infected patients in seven pilot sites in Zimbabwe

Abstract: Setting: Seven pilot sites in Zimbabwe implementing 6 months of isoniazid preventive therapy (IPT) for people living with the human immunodeficiency virus (PLHIV). Objectives: To determine, among PLHIV started on IPT, the completion rates for a 6-month course of IPT and factors associated with non-adherence. Design: A retrospective cohort study. Results: Of 578 patients, 466 (81%) completed IPT. Of the 112 patients who failed to complete IPT, 69 (60%) were lost to follow-up, 30 (27%) stopped treatment with no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
48
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(73 citation statements)
references
References 17 publications
(20 reference statements)
24
48
1
Order By: Relevance
“…First, there is need to improve early and universal access to DST (in Zimbabwe and elsewhere in SADC) for at least rifampicin, in line with the WHO End TB strategy (STOP TB Partnership 2015). Second, since isoniazid prophylactic therapy (IPT) has been scaled up in Zimbabwe with !20,000 PLHIV having been started on IPT by December 2015 and IPT completion rates of !89% have been attained (Takarinda et al 2017(Takarinda et al , 2019, and within the context of South African isoniazid-mono resistance of [4.9%, 95% CI: 4.1%-5.8%)],(National Institute for Communicable Diseases 2014) estimating the prevalence of and continued monitoring of isoniazid mono-resistance should be prioritized in Zimbabwe. Third, although sample size was small and should be interpreted as hypothesis-generating, we noted an increased risk of RR-TB among older children and adolescents, and warrants additional studies examining the determinants of childhood RR-TB in Zimbabwe.…”
Section: Discussionmentioning
confidence: 99%
“…First, there is need to improve early and universal access to DST (in Zimbabwe and elsewhere in SADC) for at least rifampicin, in line with the WHO End TB strategy (STOP TB Partnership 2015). Second, since isoniazid prophylactic therapy (IPT) has been scaled up in Zimbabwe with !20,000 PLHIV having been started on IPT by December 2015 and IPT completion rates of !89% have been attained (Takarinda et al 2017(Takarinda et al , 2019, and within the context of South African isoniazid-mono resistance of [4.9%, 95% CI: 4.1%-5.8%)],(National Institute for Communicable Diseases 2014) estimating the prevalence of and continued monitoring of isoniazid mono-resistance should be prioritized in Zimbabwe. Third, although sample size was small and should be interpreted as hypothesis-generating, we noted an increased risk of RR-TB among older children and adolescents, and warrants additional studies examining the determinants of childhood RR-TB in Zimbabwe.…”
Section: Discussionmentioning
confidence: 99%
“…WHO recommends the completion of at least six months IPT for the successful prevention of active tuberculosis among PLHIV (4,10). Globally, six-month IPT completion has been reported to range from 39-99% (28)(29)(30)(31)(32)(33)(34)(35)(36)(37), and in Tanzania studies reported 65%-98% of those who initiated IPT, completed the six month treatment course (6,20,(38)(39)(40). Most epidemiological studies have shown that IPT completion reduces the risks of mortality among PLHIV (8,26,41)…”
Section: Introductionmentioning
confidence: 99%
“…Education is an important issue but it is not the only impediment faced by health‐care workers trying to deliver IPT to children in TB‐endemic settings. Some health‐care centres lacked the equipment to rule out active TB, which they saw as necessary to initiating IPT, while others encountered supply chain difficulties in procuring sufficient isoniazid to provide patients . The labour‐intensive preparation of paediatric doses was reported as placing additional strain on already stretched staffing arrangements in some areas although child‐friendly dispersible formulations are now becoming available in most countries through the Global Development Fund .…”
Section: Discussionmentioning
confidence: 99%
“…The labour‐intensive preparation of paediatric doses was reported as placing additional strain on already stretched staffing arrangements in some areas although child‐friendly dispersible formulations are now becoming available in most countries through the Global Development Fund . Centres also often eschewed from recommending monthly monitoring, as advised by the WHO, complicating efforts to track and encourage adherence . The lack of prioritisation for IPT by government in some areas, adds another layer of difficulty to the effective implementation of these programmes, particularly in resource‐poor regions where health systems are in need of broad strengthening across multiple areas…”
Section: Discussionmentioning
confidence: 99%